Brittle failure in RC masonry infilled frames: The role of infill overstrength. (15th December 2018) - Blasi, Gianni; De Luca, Flavia; Aiello, Maria Antonietta
Highlights: Cyclic numerical modelling of brittle failures in RC frames with masonry infills. New combination of modelling approaches in OpenSees for masonry and RC columns. Calibration of proposed model through experimental tests from literature. Novel proposal for overstrength factor (Vmax /Vcr ) for hollow and solid infills. Statistical analysis on 98 test database to validate the proposed overstrength. Abstract: The interaction between an infill panel and a reinforced concrete (RC) column can lead to the brittle failure of the structural element. A novel combination of cutting-edge analytical modelling approaches for masonry infills and RC elements is employed to simulate five experimental tests (three infilled and two bare) characterized by brittle failure modes. The infill is modelled with a multi-strut idealisation, and the RC column is modelled using the recently developed PinchingLimitStateMaterial in OpenSees. The effects of the infill type (solid or hollow) and ductility characteristics of the RC elements on the optimal modelling parameters are investigated. The focus of this study is on the assumption of the overstrength ratio between the maximum and cracking strengths of the panel when brittle failure occurs. The preliminary assumption for this parameter is the widely accepted value of 1.3 suggested in the formulation by Panagiotakos and Fardis. This value is found to influence the shear failure simulation. To more accurately predict brittle failure, higher overstrength values of the infill are used in the numerical model to improve the matching between the numerical and experimental tests. These values are then compared with the approximate estimation of the overstrength ratio from a database of 98 experimental tests. The suggested estimation of the overstrength ratio is systematically greater than 1.3 and dependent on the infill type (i.e., 1.44 for hollow and 1.55 for solid infills). The proposed values can have a high impact on future code-compliant recommendations aimed at verifying the likelihood of the occurrence of brittle failure in columns due to their interaction with infill panels.